PENGEMBANGAN LEMBAR KERJA SISWA (LKS) DENGAN MATERI TRANSFORMASI GEOMETRI BERBASIS ETNOMATEMATIKA: TENUNAN SUMBA TIMUR - Wani, Salira; Hartati, Sulis Janu; Setiawan, Windi (Universitas Batanghari Jambi, 2024)
This research is an ethnomathematics-based worksheet development research on East Sumba woven materials on geometric transformations. The purposes of this study were 1) To find out the steps for developing Student Worksheets (LKS) with ethnomathematics-based geometry transformation material: East Sumba weaving using the ADDIE design. 2) To find out the feasibility of developing Student Worksheets (LKS) with ethnomathematics-based geometry transformation material: East Sumba weaving uses the ADDIE design. This research is a development research (R&D) using the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation. However, this research only reached the Development stage because it was adjusted to the research objective, namely to determine the feasibility of worksheets. At the Analysis stage, the researcher conducted a needs analysis, curriculum analysis. At the Design stage the researcher designed the LKS. At the Development stage the researcher develops worksheets and validates experts, namely media experts and material experts. The average percentage of expert validation results is 88.46%, which means that the student worksheet (LKS) based on ethnomathematics woven in East Sumba is very feasible.